Effects of heat transfer in jig molds in injection casting / Hussam Abdulla Moussa Mouhanna - Hussam Abdulla Moussa, Mouhanna (2019)
Injection Molding is a widely used process in the manufacturing industry. One of its limitations is the design of cooling channels in molds. Traditionally, only straight channels could be drilled in molds thereby providing non-uniform cooling. Additive manufacturing provides a means to create conformal channels that fit the needs of specific designs previously implausible to create. This study seeks to study the effect of conformal cooling channels in the injection molding of Tin jigs and optimize the parameters of the channels to minimize the cooling time and expedite the cooling process. This is done by exploring the effect of different design parameters of the channels using simulations. The thermal transient model is used in ANSYS 19.1 R1 to run the simulations and obtain results. These would then be analyzed using the Taguchi method to see their effects. The results showed a 28.8% decrease in cooling time with the conforming channels. Additionally, the diameter was found to be the most important factor followed by the pitch while the length was found to have a minor effect. The Taguchi method was then used to optimize and select the best parameters. Comparisons between straight and conformal channels were carried out and showed that conformal channels provide better cooling and more uniform temperature distribution.